New technique for construction of tissue heart valves. - Manothaya, C (1980)
A new technique for the construction of frame-supported tissue heart valves made of dura mater is presented. Three symmetrical pieces of pentagon-shaped tissue are used instead of the conventional quadrangular shape. A symmetrical trileaflet valve with adequate coaptation and less spherical formation of the cusps is obtained. The design characteristics suggest that regurgitation through the valve will be prevented, there will be less resistance to flow, and less strain on the leaflets during closure. This technique has been applied clinically in 37 patients with very satisfactory early results. A longer follow-up of the patients is necessary for comparison of the results with other techniques of construction.